PEUT- ÊTRE QU’UN JOUR ON VA COMPRENDRE OU PEUT-ÊTRE QU’UN JOUR ON COMPRENDRA … LA DIFFÉRENCE FONCTIONNELLE ENTRE LES DEUX FORMES DU FUTUR EN FRANÇAIS - Lebas-Frączak, Lidia (Neofilolog, 2019)
This article presents an analysis of two types of future tense in French within an “intersubjective” approach as an alternative to descriptions based on “objective” or “subjective” considerations. We put forward a hypothesis that the composed form (e.g. on va comprendre) focalizes the verb or the predicate, whereas the simple form (e.g. on comprendra) allows to “defocalize” the verb in order to indicate that the interlocutor’s attention is to be focused elsewhere: either on another part of the predicate (e.g. a complement) or on another part of the utterance, beyond the predicate or even beyond the given sentence. We show that the objective and subjective considerations used to describe these forms may be reinterpreted within the intersubjective approach and concealed with the proposed notion of “(de)focalization”.